PEMBERDAYAAN MASYARAKAT DESA SEMBALUN KABUPATEN LOMBOK TIMUR DALAM MENGEMBANGKAN POTENSI EKOWISATA - Erdianti, Baiq Nona; Pitriana, Dewi; Nazila, Dian; Pebriani, Dwi Amrina; Samudra, Gusti Bagus Aril Baghiz; Putriana, Intan; Kurniawan, Lalu Martahadi Trisna; Jannah, Miftahul; Ariyanto, Nova; Hidayatullah, Sarif; Haryanto, Hery (Universitas Mataram, 2024)
Sembalun Village is one of 6 villages and sub-districts in Sembalun District, East Lombok Regency, West Nusa Tenggara. Sembalun Village is at an altitude of 1,150 meters above sea level and borders Sembalun Lawang Village and Sajang Village in Sembalun District, East Lombok Regency, West Nusa Tenggara Province. Sembalun Village was previously part of Sembalun Lawang Village. However, after the expansion of the village by the Regent of East Lombok in 2013, Sembalun Village stood alone because it met the requirements and eligibility as a village. Sembalun Village has hilly geographical conditions and the results of field surveys show that this village is one of the tourist villages visited by many tourists. The potential for developing ecotourism edu areas is very high due to the lack of tourist areas as well as land to preserve ecology in Sembalun Village. The program will be implemented to help the community develop ecotourism potential in Sembalun Village. The UNRAM KKN-PMD team will focus on managing land suitable for use as ecotourism land. Furthermore, there will be outreach related to ecotourism so that people become more familiar with and understand the potential for ecotourism in Sembalun Village